PEMBERDAYAAN KARANG TARUNA DESA KEMUJA DALAM PENGEMBANGAN AGRIBISNIS BERBASIS DIGITAL MENGGUNAKAN CANVA - Muharani, Laily; Silalahi, Parulian; Andriyanto, Sidhiq; Yulianto, Yulianto; Agasti, Albi; Raihan Asshadqi, Muhammad (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to empower the karang taruna of Kemuja village through digital marketing training for agricultural products using Canva. Kemuja village still faces challenges in effectively developing their agribusiness. To address this issue, we conducted a training program focused on enhancing digital graphic design skills and marketing strategies using Canva. The training was held at the Kemuja village office, involving 11 Karang Taruna members as primary participants. The program included theoretical sessions on the basics of digital marketing and hands-on practice using Canva to create promotional materials such as posters, brochures, social media content, and more. The training methods included lectures, group discussions, and practical exercises, with the goal of enabling participants to optimally use Canva to expand their product promotions in the digital market. The evaluation of the training activity was conducted using a Likert scale-based instrument with 20 items, where the scale values are: 1. Strongly Disagree; 2. Disagree; 3. Neutral; 4. Agree; 5. Strongly Agree. The average score of participant satisfaction was 4.58 out of 5, indicating that the participants found the training very beneficial and relevant for their agribusiness development. In conclusion, the empowerment of the karang taruna of Kemuja village through Canva training has proven effective in enhancing their digital skills and marketing capacity, ultimately supporting the development of digital-based agribusiness in the village.